2022
DOI: 10.3390/biomedicines10030614
|View full text |Cite
|
Sign up to set email alerts
|

Development and Biological Characterization of a Novel Selective TrkA Agonist with Neuroprotective Properties against Amyloid Toxicity

Abstract: Neurotrophins are growth factors that exert important neuroprotective effects by preventing neuronal death and synaptic loss. Nerve Growth Factor (NGF) acts through the activation of its high-affinity, pro-survival TrkA and low-affinity, pro-apoptotic p75NTR receptors. NGF has been shown to slow or prevent neurodegenerative signals in Alzheimer’s Disease (AD) progression. However, its low bioavailability and its blood–brain-barrier impermeability limit the use of NGF as a potential therapeutic agent against AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 80 publications
0
17
0
Order By: Relevance
“…Considering a wider perspective, our study suggests that MNTs can contribute to combinatorial treatments for CNS injuries by simultaneously enhancing cell therapies and modulating the loss of neuronal tissue. MNT contribution in such treatments could be further enhanced by optimizing MNT dosing, exploiting novel MNT designs that target specific neurotrophin receptors [ 67 , 68 ] or utilizing targeted methods to control their spatiotemporal delivery within CNS lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Considering a wider perspective, our study suggests that MNTs can contribute to combinatorial treatments for CNS injuries by simultaneously enhancing cell therapies and modulating the loss of neuronal tissue. MNT contribution in such treatments could be further enhanced by optimizing MNT dosing, exploiting novel MNT designs that target specific neurotrophin receptors [ 67 , 68 ] or utilizing targeted methods to control their spatiotemporal delivery within CNS lesions.…”
Section: Discussionmentioning
confidence: 99%
“…It can also interact with p75NTR, inducing the recruitment of effector proteins RIP2 and TRAF6 to the receptor and the release of RhoGDI in primary granular cells of the cerebellum, as well as inducing neuroprotective effects [17]. Recently, Rogdakis et al showed that ENT-A013, which is a chemically stable and more potent compound than BNN27, selectively activates TrkA receptor and exerts neuroprotective and anti-amyloid actions [20].…”
Section: Discussionmentioning
confidence: 99%
“…Although it activates both TrkB and p75NTR neurotrophin receptors, it exerts differential signaling and cellular effects in a cell-specific manner, depending on which receptor is expressed and, surprisingly, the species origin-mouse or human-of the neuronal cell. Notably, ENT-A044 is a compound that is structurally similar to ENT-A013, which is a well characterized TrkA activator derived from the same synthetic procedures [20]. However, ENT-A044 cannot activate TrkA, as is obvious from the total absence of phosphorylation of Akt and Erk kinases, which are the most significant downstream signals of the TrkA receptor in TrkA-expressing PC12 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with the action of BDNF-related agonists against neural toxicity, the potential effectiveness of TrkA (or NGF) agonists has not been adequately demonstrated. Rogdakis et al has shown that ENT-A013, a novel NGF mimetic, selectively activates the TrkA receptor [ 53 ]. Due to NGF’s low bioavailability and its impermeability through the blood–brain-barrier, it has been considered that the use of NGF as a potential therapeutic agent against neurodegenerative diseases, including AD, was limited.…”
Section: Neurotrophin Synaptic Function and Neurogenesismentioning
confidence: 99%